Hubungan Kecerdasan Intrapersonal dan Hasil Belajar Matematika Siswa Kelas V SD Gugus II - Fayzah Fatimah; Rahmawati Patta; Abd Kadir A; Yonathan Pasinggi (Universitas Negeri Makassar, 2021)
The problem in this study is the lack of students' understanding of the intrapersonal intelligence that exists in themselves so that students are not able to know themselves well. This research is a quantitative research with correlation design. Which aims to determine the relationship between intrapersonal intelligence and mathematics learning outcomes for fifth grade elementary school students in cluster II. The results showed that there was a significant relationship between intrapersonal intelligence and mathematics learning outcomes for fifth grade elementary school students in Cluster II with tCount (6.2128) greater (>) ttable value (1.6621), which means H0 is rejected and H1 is accepted. Based on the analysis of the data above, it can be concluded that students' intrapersonal intelligence will have an impact on students' thinking in learning so that it will affect their motivation and learning outcomes in the classroom. So, the higher the intrapersonal intelligence it will improve student learning outcomes. From these conclusions, the impact resulting from this study is known that high intrapersonal intelligence will improve student learning outcomes.